2019
DOI: 10.3390/ijerph16162935
|View full text |Cite
|
Sign up to set email alerts
|

Healthy for Life Pilot Study: A Multicomponent School and Home Based Physical Activity Intervention for Disadvantaged Children

Abstract: The study aimed to develop and evaluate a multicomponent school and home based physical activity (PA) intervention in children in grades 3–7 (aged 8–13 years) and determine the psychological variables that influence PA; 10 × 1 h school-based training sessions, a home-based activity program and 4 × 1 h lifestyle workshops for parents. PA was assessed at an intervention and nearby control school using accelerometers and self-report at 3-time points: baseline, post intervention and 10-week follow-up. Self-efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 47 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…Of the 22 studies included in the review, one was classified as having strong methodological quality, 21 eleven with moderate methodological quality, 22 - 32 and ten with poor quality. 33 - 42 In terms of parameters evaluated, in the selection of bias, only 4 studies were evaluated as good, 21 , 25 , 28 , 32 because they are considered representative of the target population with a participation rate of over 80%. Study designs were classified as strong when RCTS or Controlled Clinical Trials (n=12) 21 - 26 , 28 , 29 , 32 , 33 , 38 , 39 and fair when they were Cohort analytic, case-control, cohort, or an interrupted time series (n=10).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 22 studies included in the review, one was classified as having strong methodological quality, 21 eleven with moderate methodological quality, 22 - 32 and ten with poor quality. 33 - 42 In terms of parameters evaluated, in the selection of bias, only 4 studies were evaluated as good, 21 , 25 , 28 , 32 because they are considered representative of the target population with a participation rate of over 80%. Study designs were classified as strong when RCTS or Controlled Clinical Trials (n=12) 21 - 26 , 28 , 29 , 32 , 33 , 38 , 39 and fair when they were Cohort analytic, case-control, cohort, or an interrupted time series (n=10).…”
Section: Resultsmentioning
confidence: 99%
“…Study designs were classified as strong when RCTS or Controlled Clinical Trials (n=12) 21 - 26 , 28 , 29 , 32 , 33 , 38 , 39 and fair when they were Cohort analytic, case-control, cohort, or an interrupted time series (n=10). 27 , 30 , 31 , 34 - 37 , 40 - 42 Regarding confounders parameter, 9 studies reported no baseline differences between groups 22 , 23 , 25 , 26 , 30 - 32 , 37 , 39 and 8 studies accounted for at least 80% with significant confounders. 21 , 24 , 27 - 29 , 33 , 36 , 38 Cohorts and other types of interventions performed with only 1 group were not considered.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, improvements in fitness and MVPA in interventions may be limited by using the primary aim of improving MVPA (121,126,127,129,134). Holding MVPA as the gold standard of activity may be limiting how activity is promoted to teenagers.…”
Section: Implications Of Active For Promoting Fitness and Physical Activitymentioning
confidence: 99%